2022
DOI: 10.1186/s12933-022-01606-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between the triglyceride–glucose index and severity of coronary artery disease

Abstract: Background The triglyceride–glucose (TyG) index, which is a reliable surrogate marker of insulin resistance (IR), has been associated with cardiovascular diseases. However, evidence of the impact of the TyG index on the severity of coronary artery disease (CAD) is limited. This study investigated the relationship between the TyG index and CAD severity of individuals with different glucose metabolic statuses. Methods This study enrolled 2792 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 42 publications
6
52
0
Order By: Relevance
“…Moreover, multi-vessel coronary artery disease is a type of CHD with a high risk of adverse events [5]. An elevated TyG index is associated with a significantly higher risk of multi-vessel coronary artery disease [10]. However, whether this association exists in critically ill patients with CHD, who have more severe pathophysiological conditions, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multi-vessel coronary artery disease is a type of CHD with a high risk of adverse events [5]. An elevated TyG index is associated with a significantly higher risk of multi-vessel coronary artery disease [10]. However, whether this association exists in critically ill patients with CHD, who have more severe pathophysiological conditions, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a large-scale retrospective analysis conducted in South Korea revealed that the group with the highest TyG index had a higher risk of stroke and myocardial infarction [ 31 ]. On the other hand, Su et al [ 13 ] demonstrated that TyG index was associated with CAD severity, while Wang et al [ 2 ] showed that TyG index, as an indicator for evaluating IR, may be a valuable predictor of CAD severity. Our results were consistent with findings from the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that drug interventions, such as hypoglycemic agents, antiplatelet drugs, lipid-lowering drugs and antihypertensive drugs, may affect the results [ 39 , 40 ]. However, some studies also revealed that TyG index and METS-IR were still predictors of CAD after adjusting for the effect of drugs [ 2 , 13 , 14 ]. Medication history was not included in our study due to lack of detailed data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations